Individual Differences in Performance Speed Are Associated With a Positivity/Negativity Bias. An ERP and Behavioral Study - Taroyan, Naira A.; Butnicu, Beatrice; Ypsilanti, Antonia; Overton, Paul G. (Frontiers in Behavioral Neuroscience, 2020)
There is current dispute over the origins, incidence and development of Positivity Bias, i.e., preferential processing of positive relative to negative information. We addressed this question using a multi-method technique of behavioural, psychometric and event related potential (ERP) measures in a lexical decision task (LDT). Twenty four university students (11 female) participated (age range 18-26), but 4 were omitted owing to data issues. Participants were classified as Positivity Biased (PB) if their LDT responses to positive words were faster than to negative words, and vice versa for those classified as Negativity Biased (NB), leading to a group of 11 PB participants and a group of 9 NB participants. Interestingly, the PB group was significantly faster overall than the NB group and had significantly shorter P2 component ERP latencies in the left occipital region. Furthermore, the PB group had significantly higher scores for Expressive Suppression, together with higher scores for Crystallised Knowledge and for Cognitive Reappraisal. These results suggest that around 55% of the students had Positivity Bias, and these were more efficient in processing information and had better emotion regulation abilities than those with a Negativity Bias.